IMPACT OF CONTINUOUS LEARNING ON EMPLOYEE SATISFACTION IN THE MANUFACTURING FIRMS - OBRIRHE , Ekevwehero Francis; ARUBAYI , Demaro; KIFORDU , A. Anthony (Economics and Statistics Research Journal (ESRJ), 2024)
The study examined the impact of continuous learning on employee satisfaction. Three research questions and two hypotheses were formulated to achieve the study's objectives. Literature in respect to the subject matter was reviewed. The study adopted a descriptive survey design. The population was 297, comprising all employees of Vintex Aluminum Asaba, Life Flour Mill Sapele, Differential Aluminum and Nelux Paint Benin. The sample size used for data analysis is 162. The questionnaire was used as an instrument for data collection. The data collected from the administration of the questionnaire was analyzed using descriptive and inference statistics. The study's findings revealed a significant relationship between continuous learning and employee satisfaction; there is a significant relationship between dialogue and inquiring and employee satisfaction. It was concluded that there is a significant impact of constant learning, dialogue and inquiring on employee satisfaction. Learning organizations help employees learn, give time to support education, and reward employees for learning. It was so urged, among others, that companies should maintain a culture of continual learning.